Pension fund investment management - Fabozzi, Frank J. (New Hope, Pennsylvania: F.J. Fabozzi, 1997)
Every investment professional involved with the management of pension funds will embrace this wide-ranging handbook. Consisting of articles by an esteemed panel of contributors, it covers the basics as well as the latest on pension fund governance, operations, and value creation.
Includes bibliographical references and index.
lje 25/08/16
Loan
Keywords: Pension trusts; Pension trusts - investments; Pensions; Investments; United States